1999
DOI: 10.1074/jbc.274.49.34742
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Adenylyl Cyclase by Acyclic Nucleoside Phosphonate Antiviral Agents

Abstract: Acyclic derivatives of adenine, known as highly effective nucleotide analogs with broad spectrum antiviral activity, were evaluated for potential cross-reactivity with adenylyl cyclases, a family of membrane-bound enzymes that share putative topologies at their catalytic sites with oligonucleotide polymerases and reverse transcriptases. A series of derivatives of 9-(2-phosphonylmethoxyethyl)adenine (PMEA) inhibited a preparation of adenylyl cyclase derived from rat brain with IC 50 values that ranged from 66 M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
22
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 34 publications
1
22
0
Order By: Relevance
“…However, as an off-target effect, certain antiviral compounds such as foscarnet and acyclic nucleoside phosphonates may inhibit mACs under clinical conditions (Shoshani et al, 1999;Kudlacek et al, 2001). It has been proposed that lithium and carbamazepine, mood stabilizers used for the treatment of bipolar disorder (Harwood and Agam, 2003), may act via preferential inhibition of AC5 (Mann et al, 2009).…”
Section: A General Aspectsmentioning
confidence: 99%
“…However, as an off-target effect, certain antiviral compounds such as foscarnet and acyclic nucleoside phosphonates may inhibit mACs under clinical conditions (Shoshani et al, 1999;Kudlacek et al, 2001). It has been proposed that lithium and carbamazepine, mood stabilizers used for the treatment of bipolar disorder (Harwood and Agam, 2003), may act via preferential inhibition of AC5 (Mann et al, 2009).…”
Section: A General Aspectsmentioning
confidence: 99%
“…Foscarnet 131 and antiviral acyclic nucleoside derivatives of 9-(2-phosphonylmethoxyethyl)adenine 132 proved to be potent inhibitors of nucleotidyl cyclases, and these compounds may provide novel ideas for the development of specific inhibitors.…”
Section: Atypical Ac Inhibitorsmentioning
confidence: 99%
“…Recently, benzyloxybenzaldehyde analogs (Chang et al, 2001) and antiviral drugs, such as acyclic nucleotide phosphonates (Shoshani et al, 1999) and pyrophosphate analogs (Kudlacek et al, 2001), have also been shown to directly modulate AC activity.…”
mentioning
confidence: 99%